2011
DOI: 10.3390/s110201297
|View full text |Cite
|
Sign up to set email alerts
|

Active Integrated Filters for RF-Photonic Channelizers

Abstract: A theoretical study of RF-photonic channelizers using four architectures formed by active integrated filters with tunable gains is presented. The integrated filters are enabled by two- and four-port nano-photonic couplers (NPCs). Lossless and three individual manufacturing cases with high transmission, high reflection, and symmetric couplers are assumed in the work. NPCs behavior is dependent upon the phenomenon of frustrated total internal reflection. Experimentally, photonic channelizers are fabricated in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Multiple laser sources, modulators, amplifiers, couplers, resonators, gratings, and PDs can be integrated on a monolithic chip of the size of a square millimeter or less. As an example, a photonic microwave channelizer comprised of active integrated filters was fabricated on a single chip on InP wafer with a size of ∼9 mm for coupler separation , with the assistance of microelectronic processing techniques. Integrated lenses, resonators, and nonlinear waveguides have also been employed to perform spectrum analysis and IFM [, ].…”
Section: Future Prospectsmentioning
confidence: 99%
“…Multiple laser sources, modulators, amplifiers, couplers, resonators, gratings, and PDs can be integrated on a monolithic chip of the size of a square millimeter or less. As an example, a photonic microwave channelizer comprised of active integrated filters was fabricated on a single chip on InP wafer with a size of ∼9 mm for coupler separation , with the assistance of microelectronic processing techniques. Integrated lenses, resonators, and nonlinear waveguides have also been employed to perform spectrum analysis and IFM [, ].…”
Section: Future Prospectsmentioning
confidence: 99%
“…In principle, these coefficients can vary from coupler to coupler. In this work we take them to be the same, since in the results reported in [1], this was in force (see [1] also, however, for the state space description when these coefficients can vary from coupler to coupler).…”
Section: State Space Model For the Filtermentioning
confidence: 99%
“…The study in [1] showed that the gains can be used to tune the behavior of the filter. The selection of gains in [1], however, was somewhat ad hoc.…”
Section: State Space Model For the Filtermentioning
confidence: 99%
See 2 more Smart Citations